National health insurance accreditation pattern among private healthcare providers in Ghana - Abena Agyeiwaa Lamptey; Eric Nsiah-Boateng; Samuel Agyei Agyemang; Moses Aikins (BMC, 2017)
Abstract Background Healthcare providers' accreditation is one of the standard means of assuring quality services. This paper examines the pattern of National Health Insurance Scheme accreditation results among private healthcare providers in Ghana. Methods A cross-sectional quantitative analysis of administrative data from seven National Health Insurance Scheme healthcare provider accreditation surveys over the 2009-2012 period. Data on private healthcare providers that applied for formal accreditation between the study period were retrieved from the NHIS accreditation database using a checklist. Proportions were used to examine pattern of private healthcare provider accreditation results by region, type of care provider, and grade. Results Overall, 1600 healthcare providers applied for accreditation over the study years, of which 1252 (78%) passed and were accredited. Majority of healthcare providers that passed the healthcare facility assessment were in Ashanti, Greater Accra, and Western regions, and were significantly higher than those in the other regions. Among the healthcare providers that passed the assessment, pharmacies (22%) and clinics (18%) constituted the largest groups, and were significantly higher than the other types of healthcare providers. Similarly, among those that passed, majority (62%) obtained grade C and D, representing a score of 50-59% and 60-69%, respectively, and were significantly higher than those that obtained the top three grades of A+ (90-100%), A (80-89%) and B (70-79%). Conclusions Majority of healthcare providers accredited to provide services to the insured are concentrated in three regions of the country, and are mainly pharmacies and clinics. Moreover, substantial proportion of the healthcare providers obtain average scores of the healthcare facility assessment, an indication that these care providers fall below the National Health Insurance Scheme applicable-predetermined standards.